A hybrid steganography technique based on RR, AQVD, and QVC. Issue 4 (4th July 2022) - Sonar, Reshma; Swain, Gandharba
ABSTRACT: Pixel value differencing (PVD) steganography techniques suffer with "fall off boundary problem, " and adaptive PVD (APVD) steganography techniques suffer with "unused blocks" problem. To avoid these problems, this research article describes a new steganography technique based on remainder replacement (RR), adaptive quotient value differencing (AQVD), and quotient value correlation (QVC). It performs embedding and extraction operation on 3-by-3 disjoint pixel blocks. From the 3-by-3 size pixel block two new blocks are derived: (i) the remainder block and (ii) the quotient block. Each remainder in 3-by-3 remainder block is decimal equivalent of two binary bits, so it is substituted by decimal equivalent of two secret bits. Each quotient in 3-by-3 quotient block is decimal equivalent of six binary bits. AQVD procedure is used to conceal data in four corner quotients of the quotient block. In three quotients of the middle row of the 3-by-3 quotient block, QVC embedding procedure is applied to hide the secret bits. The average hiding capacity is 3.21 bits per byte and the average peak signal-to-noise ratio is 35.27dB. Furthermore, regular-singular and pixel difference histogram attacks could not detect this technique.